1999
DOI: 10.1002/(sici)1522-726x(199908)47:4<504::aid-ccd23>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with the V-Flex Plus coronary stent: Immediate and one-month clinical outcome

Abstract: Procedural and 1‐month outcome data following implantation of the V‐Flex Plus stent in our first 54 consecutive patients (35 male; mean age, 62 years) are described. Sixty‐four stents were implanted for 60 mainly complex lesions; 48% were left anterior descending; 20%, circumflex; 27%, right coronary artery; and 5%, saphenous vein graft. The indication for stenting was elective in half of the patients and for a suboptimal result or as a bailout procedure in the other half. The stents were deployed at a mean of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is a polished polymer-free metal stent with paclitaxel (2.7 μg/mm 2 ) coated on the adluminal exterior. , The V-Flex plus stent showed initial clinical success in a pilot trial. However, late studies showed it to be inferior to polymer-based stents in preventing restenosis and cardiac events, which may be due to significant drug loss during the stent delivery and rapid release of the remaining drug, thus leading to attenuated effectiveness of the stent in suppression of neointimal formation. ,, The Supra-G and Achieve stents are similar to the V-Flex design and were also developed by Cook Inc. The Supra-G stent was shown to be safe and effective in a clinical trial addressing de novo coronary lesions, but the Achieve stent did not sufficiently decrease restenosis and revascularization compared to a bare metal stent. , …”
Section: In Vivo Application Of Polymer-free Desmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a polished polymer-free metal stent with paclitaxel (2.7 μg/mm 2 ) coated on the adluminal exterior. , The V-Flex plus stent showed initial clinical success in a pilot trial. However, late studies showed it to be inferior to polymer-based stents in preventing restenosis and cardiac events, which may be due to significant drug loss during the stent delivery and rapid release of the remaining drug, thus leading to attenuated effectiveness of the stent in suppression of neointimal formation. ,, The Supra-G and Achieve stents are similar to the V-Flex design and were also developed by Cook Inc. The Supra-G stent was shown to be safe and effective in a clinical trial addressing de novo coronary lesions, but the Achieve stent did not sufficiently decrease restenosis and revascularization compared to a bare metal stent. , …”
Section: In Vivo Application Of Polymer-free Desmentioning
confidence: 99%
“…However, late studies showed it to be inferior to polymer-based stents in preventing restenosis and cardiac events, which may be due to significant drug loss during the stent delivery and rapid release of the remaining drug, thus leading to attenuated effectiveness of the stent in suppression of neointimal formation. 18,55,65 The Supra-G and Achieve stents are similar to the V-Flex design and were also developed by Cook Inc. The Supra-G stent was shown to be safe and effective in a clinical trial addressing de novo coronary lesions, but the Achieve stent did not sufficiently decrease restenosis and revascularization compared to a bare metal stent.…”
Section: ■ In Vivo Application Of Polymer-free Desmentioning
confidence: 99%